VISUAL TEACHING OF THE TOPIC "STRUCTURE OF CRYSTALLINE BODIES" WITH THE HELP OF THE MAPLE SOFTWARE PACKAGE - Turaeva Lolakhon Yuldashevna, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This article discusses the topic of the structure of crystalline bodies, which makes it difficult for readers to understand the clarity using the “Maple” software tool.